Wannier functions of cumulene: A tight-binding approach - Ribeiro, Allan V. [UNESP]; Nacbar, Denis R.; Bruno-Alfonso, Alexys [UNESP] (Wiley-Blackwell, 2016)
Exponentially localized Wannier functions of cumulene are calculated from the Bloch functions obtained through a tight-binding approach. Numerical results and discussions are given for the pi and sigma bands. In the latter case, the single-band Wannier functions are similar to the orbitals of a diatomic molecule, while the two-band Wannier functions resemble hybrid atomic orbitals. [GRAPHICS] Contour plot of an sp-like Wannier function of cumulene. (C) 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: carbon chains; cumulene; hybrid orbitals; tight-binding calculations; Wannier functions